A grande indústria e seu impacto sobre a estrutura urbana e a governança local: o caso de Betim/MG - Lessandro Lessa Rodrigues (2020)
From the moment they are installed, hegemonic industries have an influence on various dimensions of life in cities and their urban structure. This phenomenon was intensified with the transformations perceived in the organization of the world economy at the turn of the 1960s to 1970. The productive restructuring made possible by the new information, communication and transport technologies led to the geographical reorganization of industrial activities in global and local terms, impacting cities located in central and peripheral countries. Betim has experienced developments from this process since 1973, when the construction of FIAT Automóveis was announced. In almost fifty years, economics, society, culture, urban structure, politics, municipal management, among other particularities of life in cities, have suffered the impact of the presence of large industry. This work explores part of that universe by analyzing the changes that have occurred in the territory and in local governance. During this period, both the power coalitions established in Betim and the results of their actions in the municipality had their characteristics changed. The understanding of the local situation combined with the reading of what happens in the country and in the world allows analyzing the different coalitions of power formed in the city, and their results. Over the past few decades, regardless of the party ties of municipal governments, a path towards urban entrepreneurship has been adopted, a recurring phenomenon in several cities around the world since the restructuring of the global economy. The recent efforts of public officials in Betim have been towards establishing partnerships with the private sector, with the objective of clearly adapting the municipal urban structure to the needs of local economic development, which has led to the establishment of a pro-growth urban regime in the municipality. The management model has been modified through administrative procedures, the edition of legal instruments and the adoption of other strategies that facilitate the approximation of the business sector, especially the real estate developers of the public administration's daily life. These transformations are presented in chronological order (in the light of what was happening in the world and in the country), indicating facts that together confirm the thesis that hegemonic industries are capable of imposing structural changes in the place where they are installed, which includes their physical structure, political and administrative organization, as shown in Betim.